2017
DOI: 10.1016/j.polymer.2016.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and interlayer diffusion controlled growth and unique surface patterned growth of polyelectrolyte multilayers

Abstract: In this work, extremely high molecular weight (M w ) poly(allylamine hydrochloride) (PAH, 900K g/mol) and poly(acrylic acid) (PAA, 225 K g/mol) were selected to amplify the difference in the growth of multilayers in comparison with low M w PAA (15K g/mol) and PAH (15K g/mol). By varying the pH conditions, the PAH/PAA multilayers were fabricated via the layerby-layer (LbL) assembly in both linear and exponential growth regimes. In the linear growth regime with interlayer diffusion suppressed, high M w polyelect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…A low molecular mass will increase the risk of PE desorption at the contact with the oppositely charged PE, while a higher molecular mass will enhance the deposition of multilayers and will increase its stability. Additionally, it is generally accepted that PEMs consisting of high molecular mass PEs are more stable than PEMs based on low molecular mass PEs [ 65 , 66 , 67 ]. Studying the LbL deposition of PLL and HA, Shen et al [ 68 ] also observed that the molecular weight of HA influences the deposition of PEMs.…”
Section: Factors Controlling the Fabrication Of Multilayersmentioning
confidence: 99%
“…A low molecular mass will increase the risk of PE desorption at the contact with the oppositely charged PE, while a higher molecular mass will enhance the deposition of multilayers and will increase its stability. Additionally, it is generally accepted that PEMs consisting of high molecular mass PEs are more stable than PEMs based on low molecular mass PEs [ 65 , 66 , 67 ]. Studying the LbL deposition of PLL and HA, Shen et al [ 68 ] also observed that the molecular weight of HA influences the deposition of PEMs.…”
Section: Factors Controlling the Fabrication Of Multilayersmentioning
confidence: 99%
“…The thicknesses of the (BPEI/ARS) n , (BPEI/(PSS+ARS)) n and ((BPEI+ARS)/PSS) n films were measured using a profilometer for when n was 20, 40, 60, 80, 100 and 120 (Figure 4). All three types of assemblies showed linear growth behavior, indicating suppressed interlayer diffusion throughout the multilayer films [64]. When the bilayer number was 20, the thicknesses of (BPEI/ARS) 20 , (BPEI/(PSS+ARS)) 20 and ((BPEI+ARS)/PSS) 20 were 237, 226 and 955 nm, respectively; when the bilayer number increased to 120, the thicknesses of (BPEI/ARS) 120 , (BPEI/(PSS+ARS)) 120 and ((BPEI+ARS)/PSS) 120 reached 4620, 5840 and 9860 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This model of pore formation was further exploited to engineer porous LbL films.L ee and co-workers prepared PA A/PAH polyelectrolyte multilayer films with tunable surface properties and hierarchical pores by using highmolecular-weight PA Hand PA A. [25] Zacharia and co-workers created pores by exposing poly(ethylene imine)/PAA films to an electric field. [21] Zhang and co-workers fabricated al ightsensitive porous film, and created pores 10-100 nm in size by degradation of poly-l-lysine (PLL) and DNAterminated with 5-(4-aminophenyl)-10,15,20-triphenylporphyrin (APP) groups by irradiation with light.…”
Section: Post-treatment Methods For Porous Lbl Filmsmentioning
confidence: 99%
“…d) Top‐view SEM images of a (PAA/PAH) 20 film after immersion in an aqueous solution at pH 2.7 for 30 min without subsequent immersion in deionized water . e) SEM images of PAH 8.5 /PAA 3.5 films with 12.5 bilayers . f) Schematic illustration of the preparation and AFM images (before and after cross‐linking) of PAH/PAA porous polyelectrolyte LbL membranes .…”
Section: Porous Polyelectrolyte Membranesmentioning
confidence: 99%